Netralitas dalam kajian religiusitas di Indonesia - Subhan El Hafiz (Jurnal Psikologi Ulayat, 2021)
Religiosity studies in Indonesia is an interesting topic; however, one of the biggest challenges in studying religiosity in Indonesia is the neutrality of the researcher regardless of their attitudes toward religion. This editorial note will explore the meaning of neutrality in religiosity studies. Specifically, it emphasizes the responsibility of the researchers to understand the complexity of religion by acknowledging that religion can have a positive impact and/or negative effect on believers. Furthermore, the present note describes how studies on the psychology of religion in Indonesia can contribute to the body of knowledge not only at the local level, but also at the global context.